Contributions of dry and wet weather runoffs to annual pollutant loading in tropical urban catchments - Chow M.F.; Yusop Z. (Springer, 2023)
Ammonia; Catchments; Decision making; Land use; Storm sewers; Storms; Tropics; Water pollution; Dry weathers; Non-point source pollution; Stormwaters; Urban areas; Wet weather flow; Pollutant loadings; Potential contaminants; Relative contribution; Storm water runoff; Runoff